Unraveling the Dynamic Impact of Money Supply, Interest Rates, and Corruption on Inflation: Evidence from Indonesia - Kurniasih, Cut Endang; Budiartiningsih, Rahmita; Sari, Lapeti; Aulia, Ando Fahda; Aqualdo, Nobel; Zuryani, Hilmah (Jurnal Ekonomi Pembangunan, 2024)
This study investigates the impact of money, interest rates, and corruption on inflation in Indonesia. This data was obtained from Transparency International and the World Bank from 1995 to 2022. The Auto Regressive Distributed Lag (ARDL) model will be utilized as the estimation method. These findings reveal significant long-term relationships between the variables studied. In the long run, inflation in Indonesia is largely determined by corruption, interest rates, and the money supply. Apart from that, this significant influence is also found in short-term estimation results with different relationships. A decrease in CPI (high corruption) increases the inflation rate significantly, and vice versa. This demonstrates how crucial it is to set up strategies and policies to keep the inflation rate stable for a sustainable economy that doesn't just rely on financial tools but also lessens the likelihood of government-caused corruption and sources of income.